Quality control practices related to workmanship among selected children's wear exporting companies - Evaristo, Aleli G.
The study aimed at identifying the quality control practices related to workmanship among the selected children's wear exporting companies within the Quezon City area. The focus was divided into: (1) the general parameters: forms of garment inspection according to stage in the production flow, methods, and amount of garment inspection, and (2) the specific parameters: patch pockets, gathers, collars, buttons and buttonholes, embroidery and seams. actual inspection of garment pieces was also conducted by the researcher in every respondents company. The study employed a descriptive research design among the companies and garment pieces. A total of five children's wear exporting companies and 540 garment pieces were the subjects of the study. Observation and interview guides were used as instruments for data gathering. The results for the general and specific parameters were compared to the Philippine Trade and Training Center's (PTTC) guidelines for garment inspection and Mary Jo Kallal's suggested evaluation criteria for the workmanship of certain garment features. Upon comparison ans analysis of the results, the study showed that the five companies practiced similar quality control measures. These results were also similar to the PTTC guidelines and Kallal's suggested evaluation criteria. Generally, the results centered on the following: (1) forms of garment inspection according to stage in the production flow such as incoming inspection, patrol or roving inspection, and end-line or bench inspection, (2) garment inspection methods such as go and no-go checking measurement, functional checking and visual inspection, (3) amount of garment inspection such as sampling inspection through AQL (Acceptable Quality Level) sampling, 60-80% final inspection, and 100% inspection, and (4) sewing techniques and visual checkpoints for the workmanship of the six specific parameters. The study also found out that quality control practices were present among the companies regardless of their scale size, whether small, medium or large scale. The results of the actual inspection conducted by the researcher showed that the companies practice quality control measures extensively on the six specific parameters of the study.